Severe Thrombocytopenia in a Pregnant Patient with Asymptomatic COVID-19 Infection: A Case Report - Moses, Maya L (Cureus, 2021)
Thrombocytopenia occurs in one-third of patients with coronavirus disease 2019 (COVID-19) infection and can indicate the severity of disease and may also increase the bleeding risk of performing invasive procedures. We present a pregnant patient with COVID-19 infection with the lowest platelet count described in the literature to date. The patient presented in labor at 38 weeks gestation with no other symptoms and was found to be positive on routine COVID-19 testing. The routine complete blood count upon admission was significant for a platelet count of 6 x 10(9)/L which was rechecked and resulted in a platelet count of 8 x 10(9)/L. The etiology of her thrombocytopenia was not clear prior to delivery as preeclampsia with severe features and lupus exacerbation were also possibilities that were considered. However, after delivery it became apparent that COVID-19 likely had a significant impact contributing to her severe thrombocytopenia. Her care was complicated by postpartum hemorrhage resulting in massive transfusion. This case highlights the importance of evaluating platelet count and coagulation status in COVID-19 patients, even if asymptomatic.